Domingos Vandelli (1735-1816): história natural e utilitarismo ilustrado em fins do antigo regime português - Braga, Lucas Onorato (2023)
The emergence of Modern Science (16th-17th centuries) corresponded to a gradual process of changes in the intellectual and cultural production of Western Europe. In this context, the natural sciences became the focus of the academies, as their mastery was considered an essential source for social well-being and the field in which the power of civilized man was exercised. In Portugal, this movement gained momentum in 1764 with the arrival of the Paduan naturalist Domingos Vandelli (1735-1816), one of the effective members who formed the core of the founders of the Lisbon Academy of Sciences (1779). Their scientific production stood out for its eminently practical character. In this regard, Vandelli can be considered one of the main mentors of the actions of Portuguese institutions, as attested by his numerous publications within the scope of the University of Coimbra and the Royal Academy. In this context, the project takes as a reference the notes of Pierre Bourdieu (1998) and Sabina Loriga (1998) for the mapping of trajectories. Thus, we have chosen as the central object of this research to evaluate the importance of Domingos Vandelli in the panorama of Natural History in the second half of the 18th century in Portugal, based on his personal trajectory. In this scenario, we are interested in assessing to what extent his works fit into the Vandellian project of describing the nature of Portugal and its domains, aiming to indicate elements that would subsidize a strategy for the better use of these available resources, contributing to a more concrete action of institutions in the economic domain.